Endophytic fungi from South Sumatra (Indonesia) in seed-treated corn suppressing Spodoptera frugiperda growth (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Herlinda S, Gustianingtyas M, Suwandi S, Suharjo R, Sari JMP, Suparman, Hamidson H, Hasyim H. 2022. Endophytic fungi from South Sumatra (Indonesia) in seed-treated corn suppressing Spodoptera frugiperda growth. Biodiversitas 23: 6024-6031. The aim of this research was to evaluate the effect of endophytic fungi in seed-treated corn on S. frugiperda growth. A total of 20 isolates of endophytic fungi were molecularly identified, namely Chaetomium sp. (GaTpeOi, JgTjPr, PiCrPga, and CaCjPga isolates), Aspergillus niger (PsgTjPr, JgByU, and JaBuBys isolates), Beauveria bassiana (JgSPK, JaGiP, JaSpkPGA(2) isolates), JgCrJr, dan JaTpOi (1) isolates), Curvularia lunata (JaGiPRB, CMTJP, JaMsBys, JaSpkPga(3), and JgTgSr isolates), Aspergillus flavus (JgPWSR isolate), Penicillium citrinum (JaTpOi(2) isolate), and Metarhizium anisopliae (CaTpPGA isolate). Of the 20 isolates, 4 isolates (JgSPK, JaGiP, JgCrJr, JaTpOi (1)) of B. bassiana and one isolate of each C. lunata (JaSpkPga (3)), and M anisoplae (CaTpPga) were found to be more pathogenic to S. frugiperda larvae. The endophytic fungi had negative effect on S. frugiperda growth. B. bassiana, M. anisopliae, and C. lunata decreased the percentage of pupal and adult emergence, and the number of eggs laid by treated female adults. The fungi also shorten the adult longevity and increased the larval mortality. This is the first report of pathogenicity of C. lunata against S. frugiperda. These findings highlight the potential of endophytic fungi, namely B. bassiana, M. anisopliae, and C. lunata from South Sumatra to protect young maize plant against S. frugiperda by seed treatment.
Keywords: Beauveria bassiana, Curvularia lunata, Metarhizium anisopliae, seed treatment, Zea mays